A Global Perspective : Tackling Three 'Intractable' Challenges Facing the World - Kim, Jim Yong (2016)
Remarks delivered by Jim Yong Kim, President of the World Bank Group, at Goethe University, Frankfurt, Germany, discuss applying the world’s best ideas, knowledge, and experience in development to accomplish the World Bank Group’s twin goals of ending extreme poverty by 2030, and boosting shared prosperity. He speaks about helping the poor and vulnerable in low- and middle-income countries in the world not only for poverty reduction within their borders, but is important for growth around the world, especially going forward. He talks about the strategy to invest in people, especially through education and health. He stresses investments in girls and women as particularly important because they have a multiplier effect on the well-being of the extreme poor. He speaks about protecting people from deadly pandemics especially in developing countries. He insists the students that they must apply what they have learned, and must do, for the sake of the poorest, for the children, and for the sake of our humanity.